(untitled) (PANGEEA, 2025)
Realization of final plot plan at national level. In order to rational exploitation of land it is necessary to be represented to be as well known as size, content and form in their geographical expression. On this line preparing this plot plans aims creating resolutions and other legal documents related to the ownership, issue decisions inspection of the property change cadastral boundaries of the municipality, changing the type of plot limit, etc. The progress made in recent years in the field of cadastre require addressing this issue from a modern perspective, namely that of structuring information in accordance with the methods and instruments used ultimate goal being the completion of the work for making plot plans at national level.